An experimental investigation of the influence of media type on individual perceptions of the severity of earthquake events. (13th November 2007) - Walton, D.; Lamb, S.; Dravitzki, V.
Earthquake simulation videos were created modelling a moderate and severe event (6.8 and 7.5 respectively on the Richter Scale) in an office and home setting. A 67-mixed-item computer assisted survey was administered to 562 participants. Changes in perceptions of severity were examined over independent variables Simulated Setting, Simulated Intensity and Media Order in a 2 ? 2 ? 6 mixed design. Participants selected the viewing order of three media sources (internet, TV and radio) which depicted the scenario. Changes in perception of severity were measured by a 5-item scale (alpha = .87) after each media source. While radio was the most preferred media source prior to viewing, television was found to cause the largest increase in perceptions of severity. Viewing all media sources significantly increased perceptions of severity compared with only viewing the initial earthquake simulation video. Relative damage estimates indicated that participants' believed the earthquake was centred on their home.